2016
DOI: 10.16943/ptinsa/2016/48463
|View full text |Cite
|
Sign up to set email alerts
|

"Research Highlights on the Evolution of Precambrian Crust of Peninsular India: Constraints from Recent Zircon U-Pb Geochronological Results"

Abstract: During the last quadrennial period, (2012-2016), many aspects of the Precambrian geology of the Indian peninsula were revisited by Indian geoscientists and their collaborators with the advantage of modern analytical techniques for geochronology as well as new perspectives on global geodynamics in space and time. Important contributions were made to the Archean and Proterozoic geological evolution of the Dharwar, Singhbhum, Bundelkhand and Bastar cratons, the granulite gneiss terrains, especially the Southern G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 79 publications
0
1
0
Order By: Relevance
“…Based on this, they suggested that the Papaghni and Chitravati Groups were fed by detritus from the Dharwar craton and may have been deposited after 2.0 Ga. These and other detrital zircon ages have been used by workers to infer the 'maximum depositional age (MDA)' of the host sediments (e.g., Absar et al, 2016;Bhaskar Rao et al, 2016). It is necessary to recognize that this inference only ensures that the sediments are not 'older than the MDA' but does not provide any concrete evidence of the actual age of deposition.…”
Section: Age Of Sequencesmentioning
confidence: 99%
“…Based on this, they suggested that the Papaghni and Chitravati Groups were fed by detritus from the Dharwar craton and may have been deposited after 2.0 Ga. These and other detrital zircon ages have been used by workers to infer the 'maximum depositional age (MDA)' of the host sediments (e.g., Absar et al, 2016;Bhaskar Rao et al, 2016). It is necessary to recognize that this inference only ensures that the sediments are not 'older than the MDA' but does not provide any concrete evidence of the actual age of deposition.…”
Section: Age Of Sequencesmentioning
confidence: 99%